Representations, analysis and recognition of shape and motion from imaging data : 6th International Workshop, RFMI 2016, Sidi Bou Said Village, Tunisia, October 27-29, 2016, Revised selected papers /: 6th International Workshop, RFMI 2016, Sidi Bou Said Village, Tunisia, October 27-29, 2016, Revised selected papers. (2017) - Unknown
No abstract available